Form-focused instruction: An interview with Nina Spada - Spada, Nina; Ortega, Yecid; Banegas, Darío Luis (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
In this interview, form-focused instruction, research methods, and future research questions in SLA are discussed with Professor Nina Spada. The interview took place in December 2016 with the help of Yecid Ortega. Together with form-focused instruction, Spada reflects on the following topics: teacher research, replication studies as instances of creative research, amount of instruction with young learners, and issues in content and language integrated learning among other crucial topics in language learning.